Carotenoid characterization, fatty acid profiles, and antioxidant activities of haloarchaeal extracts - Kesbiç, Fevziye Işıl; Gültepe, Nejdet (Wiley, 2023)
AbstractMicroorganisms that can survive in saline environments, known as halotolerant or halophilic organisms, have a wide range of current and potential uses in biotechnology. In this study, it was aimed to determine the carotenoids of halophilic archaea strains isolated from the brine samples taken from different points of Salt Lake (Turkey) and determine the antioxidant activities of their carotenoids. To identify the halophilic archaea strains, they were cultivated in MAM JCM 168 medium and subjected to antibiotic susceptibility, fatty acid, two‐dimensional and three‐dimensional imaging by scanning electron microscopy and atomic force microscopy, biochemical and phylogenetic assays. The findings show that five different halophilic archaea strains have been identified as Halorubrum lipolyticum, Halorubrum sodomense, Haloarcula salaria, Halorubrum chaoviator, and Haloarcula japonica with 98% and above similarity ratio. The main fatty acids of all haloarchaeal strains were octadecanoic acid (C18:0) and palmitic acid (C16:0). The major carotenoid of the species was determined as all‐trans bacterioruberin, and different carotenoid types such as lycopene, β‐carotene, and 2‐isopentenyl‐3,4‐dehydrorodopin were found as well as bacterioruberin isomers. The antioxidant activities of carotenoids extracted from the species were analyzed by the 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging method and the extracts showed antioxidant activity statistically significantly higher than ascorbic acid and butylated hydroxytoluene as reference products (p < 0.05).
Keywords: Fatty Acids; Halorubrum; Carotenoids; Antioxidants; Phylogeny; 6. Clean water